2015
DOI: 10.1101/cshperspect.a022731
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and Epilepsy

Abstract: Epigenetic processes in the brain involve the transfer of information arising from short-lived cellular signals and changes in neuronal activity into lasting effects on gene expression. Key molecular mediators of epigenetics include methylation of DNA, histone modifications, and noncoding RNAs. Emerging findings in animal models and human brain tissue reveal that epilepsy and epileptogenesis are associated with changes to each of these contributors to the epigenome. Understanding and influencing the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 115 publications
(140 reference statements)
0
75
0
4
Order By: Relevance
“…circRNAs have been associated with neurodegenerative diseases, such as multiple sclerosis, Parkinson’s disease, Alzheimer’s disease and schizophrenia [18, 39]. In our research, bioinformatics analysis of differentially expressed circRNAs indicated that these circRNAs might be associated with pathways such as GTPase activity, protein transport, and protein phosphorylation; these pathways play key roles in the pathogenesis of epilepsy [40, 41]. …”
Section: Discussionmentioning
confidence: 99%
“…circRNAs have been associated with neurodegenerative diseases, such as multiple sclerosis, Parkinson’s disease, Alzheimer’s disease and schizophrenia [18, 39]. In our research, bioinformatics analysis of differentially expressed circRNAs indicated that these circRNAs might be associated with pathways such as GTPase activity, protein transport, and protein phosphorylation; these pathways play key roles in the pathogenesis of epilepsy [40, 41]. …”
Section: Discussionmentioning
confidence: 99%
“…Among them is an increased activity of DNA methylating enzymes leading to hypermethylation of DNA (7579). Another proposed mechanism implicates histone modifications that involve the addition or removal of methyl or acetyl groups during epileptogenesis (21). Recently, Boison (16) proposed that adenosine and glycine may regulate epigenetic mechanisms of epileptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Major epigenetic mechanisms include DNA methylation, histone modification, and microRNA-driven posttranscriptional regulation of gene expression. Methylation-dependent gene silencing is currently one of the most thoroughly investigated mechanisms for regulation of gene expression (1721). …”
Section: Epigenetic Mechanisms Control Gene Function Without Dna Mutamentioning
confidence: 99%
“…One of several mechanisms of action, VPA displays HDAC-inhibiting activity, which as expected, exerts a suppressive effect on gene transcription [235] multiple aspects of the epigenome, promoting increased H3 acetylation in the brain [264], while also facilitating the direct or indirect demethylation of DNA [265]. This ability to exert multiple effects on the epigenome likely further contributes to VPA’s effectiveness as an anti-epileptic agent.…”
Section: Epigenetic Inhibition Of Epileptogenesismentioning
confidence: 96%
“…X-chromosome inactivation in females), as control of gene expression is carried out primarily by gene silencing [235]. Investigations into epigenetic processes have revealed significant alterations to the epigenome of an epileptic brain [236,237].…”
Section: Epigenetic Inhibition Of Epileptogenesismentioning
confidence: 99%